Apolipoprotein A-IV concentrations and clinical outcomes in a large chronic kidney disease cohort: Results from the GCKD study - Schwaiger, Johannes P.; Kollerits, Barbara; Steinbrenner, Inga; Weissensteiner, Hansi; Schoenherr, Sebastian; Forer, Lukas; Kotsis, Fruzsina; Lamina, Claudia; Schneider, Markus; Schultheiss, Ulla T.; Wanner, Christoph; Koettgen, Anna; et al. (Journal of Internal Medicine, 2022)
Background Chronic kidney disease (CKD) represents a chronic proinflammatory state and is associated with very high cardiovascular risk. Apolipoprotein A-IV (apoA-IV) has antiatherogenic, antioxidative, anti-inflammatory and antithrombotic properties and levels increase significantly during the course of CKD. Objectives We aimed to investigate the association between apoA-IV and all-cause mortality and cardiovascular outcomes in the German Chronic Kidney Disease study. Methods This was a prospective cohort study including 5141 Caucasian patients with available apoA-IV measurements and CKD. The majority of the patients had an estimated glomerular filtration rate (eGFR) of 30-60 ml/min/1.73m(2) or an eGFR >60 ml/min/1.73m(2) in the presence of overt proteinuria. Median follow-up was 6.5 years. The association of apoA-IV with comorbidities at baseline and endpoints during follow-up was modelled adjusting for major confounders. Results Mean apoA-IV concentrations of the entire cohort were 28.9 +/- 9.8 mg/dl. Patients in the highest apoA-IV quartile had the lowest high-sensitivity C-reactive protein values despite the highest prevalence of diabetes, albuminuria and the lowest eGFR. Each 10 mg/dl higher apoA-IV translated into lower odds of prevalent cardiovascular disease (1289 cases, odds ratio = 0.80, 95% confidence interval [CI] 0.72-0.86, p = 0.0000003). During follow-up, each 10 mg/dl higher apoA-IV was significantly associated with a lower risk for all-cause mortality (600 cases, hazard ratio [HR] = 0.81, 95% CI 0.73-0.89, p = 0.00004), incident major adverse cardiovascular events (506 cases, HR = 0.88, 95% CI 0.79-0.99, p = 0.03) and death or hospitalizations due to heart failure (346 cases, HR = 0.84, 95% CI 0.73-0.96, p = 0.01). Conclusions These data support a link between elevated apoA-IV concentrations and reduced inflammation in moderate CKD. ApoA-IV appears to be an independent risk marker for reduced all-cause mortality, cardiovascular events and heart failure in a large cohort of patients with CKD.
CRIS-Team WoS Importer:2022-01-14